The relationship of digital payments, macroeconomic variables, and banking stability in developing Asia - Meidiana AZZAHRAH; Ariodillah HIDAYAT; Liliana LILIANA (Theoretical and Applied Economics)

(untitled)
This study examines the relationship between digital payments and macroeconomic variables on banking stability in Asian countries. This research uses data sourced from the International Monetary Fund (IMF) and the World Bank with the period 2011 to 2021. This study used panel data regression analysis techniques in the form of Fixed Effect Model. The results showed a positive and significant relationship between digital payment variables, economic growth, inflation and banking stability. The negative correlation between exchange rates and banking stability highlights the potential adverse effects of currency exchange rate fluctuations.